2011
DOI: 10.5539/jsd.v4n5p139
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Housing Development and Functionality of Planning Laws in Nigeria: the Case of Cosmopolitan Lagos

Abstract: The phenomenal growth of our towns and cities has given rise to conurbation and metropolitan areas, with various planning problems such as traffic congestion, slum, shanty towns, waste management, housing, pollution, poverty and several others. There is no doubt that the impact of rapid population growth on housing development in a developing economy is usually a consequence of the push of the rural areas and the pull of the town. There is always an upsurge and conglomeration of people in city centres with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This study identified the need for more empirical investigation into such crucial components of flood risk management in Lagos. In relation to the planning framework, sustainable housing development and functionality of planning laws and regulations as well as the role of governance in flood management in the Lagos area and indeed in Nigeria have been examined by a number of authors including Aluko (2011) andOshodi (2013).…”
Section: Recent Research Effortsmentioning
confidence: 99%
“…This study identified the need for more empirical investigation into such crucial components of flood risk management in Lagos. In relation to the planning framework, sustainable housing development and functionality of planning laws and regulations as well as the role of governance in flood management in the Lagos area and indeed in Nigeria have been examined by a number of authors including Aluko (2011) andOshodi (2013).…”
Section: Recent Research Effortsmentioning
confidence: 99%
“…It becomes necessary to allow for and ensure greater predictability in urban growth and development so as to make adequate provision for public services (Nduka and Sam-Amobi, 2013 The issues of development control in Nigeria are not new in academic discourse. Evidence from past studies such as (Mabogunje, 1986;Sanusi, 2006;Nna, Opuenebo and Ipoki, 2007;Aribigbola, 2008;Fagbohun and Odumosu 2009;Aluko 2011;Eje et al, 2011) revealed that no city in Nigeria can be regarded as a model for good planning from the point of employment, liveability, manageability and serviceability. Also studies such as (Omisore and Akande, 2004;Obabori et al 2007;Aribigbola, 2008;Ogundele et al, 2011) have examined development control in terms of strategies for implementation, procedural and compliance challenges, regulatory and capacity issues that can inform an effective implantation of development control instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to obtain a governor's consent is generally associated with incomplete documentation, irregular signatures, or other administrative bottlenecks. Obtaining approval from government offices also involves a number of direct and indirect costs, including uncertainty, corruption, travel costs to government offices, and opportunity costs such as loss of wages (Aluko 2011). Bottlenecks create lengthy delays and require undue investment from beneficiaries to be processed (Aluko 2011).…”
Section: Box 31 Intermediaries and The Cost Of Low Information On Lamentioning
confidence: 99%
“…For instance, granting a development permit by a Development Control Department must conform to the issue of Certificate of Occupancy. In addition, any revocation of acquired occupancy must be in accordance with the provisions of the LUA (Aluko 2011). Because all development takes place on land, the decree does not help to ease planning concerns since all land-related issues must be in accordance with the provisions of the LUA (Aluko 2011).…”
Section: Land Use and Urban Planningmentioning
confidence: 99%